An heart team stroke prevention decision-making process comparing percutaneous endocardial and thoracoscopic epicardial left atrial appendage occlusion. (14th October 2021) - Branzoli, S; Marini, M; Guarracini, F; D'Onghia, G; Penzo, D; Graffigna, A; Piffer, S; Bonmassari, R; La Meir, M
Abstract: Introduction: Left atrial appendage occlusion (LAAO) is a validated therapeutic option in patients with atrial fibrillation (AF) at high thrombo-embolic risk and contraindication to oral anticoagulation. Large clinical trials have demonstrated excellent efficacy of percutaneous LAAO, but also stand-alone thoracoscopic LAAO has shown promising results with the advantage of absence of antiplatelet therapy. No direct comparison of both strategies has been published yet. Purpose: To evaluate an Atrial Fibrillation Heart Team guided approach to percutaneous or thoracoscopic left appendage exclusion in patients with non valvular atrial fibrillation (NVAF). Methods: Forty patients with a contraindication to oral anticoagulation (OAC) were evaluated in the AF Heart Team for LAA exclusion. Contraindication for OAC was based upon a history of cerebral hemorrhages (n=17), non-cerebral life-threatening hemorrhages (n=9), repetitive bleeding (n=8) and having underlying diseases associated to high bleeding risk (n=6). The 20 patients included in the LAAO-Percutaneous group (LAAO-P) were on low molecular weight heparin pre-procedure, whereas in the LAAO-thoracoscopic group (LAAO-TT) none were on low molecular weight heparin nor antiplatelet therapy since the bleeding risk was estimated too high. The LAAO-P group were 70% male, with a mean age of 72.3±7.5 (range 57–82), mean CHA2DS2VASc 4.2 (range 1–6) and a mean HASBLED 3.5 (range 1–5) with an expected risk of bleeding between 3.7–8.7% per year. The LAAO-TT were 72.5% male, with a mean age of 74.9±8 (range 53–87 years), mean CHA2DS2-VASc 6.05 (range 4–8), HASBLED mean 5.4 (range3–8) expected risk of bleeding >12.5% per year. Variables considered were CHA2DS2VASc, HASBLED, documented blood transfusions, comorbidities related risk of bleeding, anatomy of the LAA, lung function, patient quality of life. LAAO-P patients were on dual antiplatelet therapy (DAT) at discharge for the first three months and aspirine 100mg/day thereafter, whereas the LAAO-TT patients were not. Follow up included TEE at 1 months and CT scan at 3 months. Results: Mean duration of procedures for LAAO-P was 54.4 minutes, for LAAO-TT 52.01 minutes, mean post procedural ventilation time was respectively 11.2±6.4 and 15.8±16.4 minutes. No major complications occurred in both groups. One patient in the LAAO-P crossed over because of an unsuitable anatomy which became apparent intra-operatively. Mean hospital stay were comparable in both groups, 3.4±0.7 and 3.8±0.9 days respectively. At mean follow up of 24.3±10.1 months (range 5–36) all patients had complete exclusion of the appendage, no neurological events were reported. Conclusions: The Heart Team can improve decision making in complex stroke prevention where LAAO is a therapeutic option, percutaneous and thoracoscopic occlusion seem to be comparably safe and effective. An epicardial LAAO could be advised in patients were the bleeding risk is estimated too high for AP therapy. Funding Acknowledgement: Type of funding sources: None.